Instructional video program for teaching self-help skills to Filipino children with autism - Madronio, Claudette M. (2008)
The study developed an instructional video program (IVP) in digital video disc (DVD) format which featured 23 self-help skills taken from Dr. Trinidad Baldo's Teaching Manual in Special Education (Self-Help Skills). Simultaneously it was validated by a pilot test group of 2 SPED teachers, 2 parents and 1 occupational therapist all handling and taking care of children with autism (CWA). The respondents were 10 teachers, 10 parents and therapists, and 10 CWA. The research findings showed that the instructional video program is a valid medium in teaching self-help skills, that it is acceptable and appropriate for use by Filipino children with autism in the preschool level for both classroom and home settings.